Hippasteria falklandica Fisher 1940 ... - Mah, Christopher L. (Zenodo, 2011)
Hippasteria falklandica Fisher, 1940 Fisher, 1940: 125; Bernasconi, 1973: 287; Clark & Downey, 1992: 247; Mein, 1992: 245; Stampanato & Jangoux, 2004: 4, 6; McKnight, 2006: 97. Occurrence. Falkland Islands (= Islas Malvinas), northern Argentina, Marion and Prince Edwards Islands region to south of Tasmania, approx. 49°S, 150°E. 225–1148 m. Description. Body stellate with arms, elongate tapering. R/r=3.8. Abactinal plates small, lobate, ovoid or irregular in outline with center of plate raised. Plates closely spaced at disk center with lobes “immersed in membrane”. Raised area of plates with granules, one to five, varying in size. If only one or two, then those granules are larger and hemispherical. Smaller granules with variable sizes and may be flattened. Large granules up to 1.5 mm in diameter. Surface covered by abundant, partly embedded bivalve or in some cases-trivalved pedicellariae, each with a narrow rim. Papulae, one to three between plates, widespread between abactinal plates, absent near ... : Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 27, DOI: 10.5281/zenodo.276783 ...